2012
DOI: 10.1097/aln.0b013e31826904a6
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Intraoperative Awareness with Explicit Recall in an Unselected Surgical Population

Abstract: Background Intraoperative awareness with explicit recall occurs in approximately 0.15% of all surgical cases. Efficacy trials based on the Bispectral Index™ (BIS) monitor and anesthetic concentrations have focused on high-risk patients, but there are no effectiveness data applicable to an unselected surgical population. Methods We conducted a randomized controlled trial of unselected surgical patients at three hospitals of a tertiary academic medical center. Surgical cases were randomized to alerting algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
176
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 252 publications
(185 citation statements)
references
References 21 publications
4
176
1
4
Order By: Relevance
“…Based on cases of awareness that became known to anaesthetists during 2011, the survey suggests that the current incidence of AWR in the UK is about 1 in 15 000. This is much lower than the 1 to 2 per 1000 incidence that has been found in several prospective studies that have assessed AWR [2][3][4]. This is not the first time the field of anaesthesia has been confronted with an investigation reporting an incidence of AWR one order of magnitude lower than that found in prospective studies.…”
Section: Editorialcontrasting
confidence: 40%
See 4 more Smart Citations
“…Based on cases of awareness that became known to anaesthetists during 2011, the survey suggests that the current incidence of AWR in the UK is about 1 in 15 000. This is much lower than the 1 to 2 per 1000 incidence that has been found in several prospective studies that have assessed AWR [2][3][4]. This is not the first time the field of anaesthesia has been confronted with an investigation reporting an incidence of AWR one order of magnitude lower than that found in prospective studies.…”
Section: Editorialcontrasting
confidence: 40%
“…It has been demonstrated that patients are unlikely to report spontaneously an AWR event to an anaesthetist [16], perhaps because of the brief interaction and limited relationship. Based on data from a single hospital complex in the US, a retrospective audit of spontaneous patient reports revealed a six-fold lower incidence of AWR [17] than a study in which patients were questioned directly [4]. Any study that relies on spontaneous patient reports of AWR rather than proactive questioning of all patients is likely to underestimate considerably the incidence of AWR.…”
Section: Editorialmentioning
confidence: 99%
See 3 more Smart Citations